Monographic Method in Sociology - Vosyliūtė, Anelė (Problemos, 1981)
In contrast to selective and complete studies where a great amount of objects with a lower number of indices are observed, in a monographic research one social object (a city or town, an enterprise, a village, a family} is described by a larger number of indices. The leading principle of the monographic method lies in the arrangement of the data of a sociological research so as to underline the unity of structural components of a social object. In the article the constructions of sociological monographs of the villages of Žmiąca and Kopanka are presented and a brief estimation of a monograph by W. Staniewicz on the village of Matuizos-Balandiškės is given.